2020
DOI: 10.7150/ijms.45400
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Inhibits Pro-inflammatory Cytokine-induced IL-6 and CCL11 Production via Modulation of STAT6 Pathway in Human Bronchial Epithelial Cells

Abstract: Berberine is an isoquinoline alkaloid isolated from various Chinese herbs that has potential of antiinflammatory, anti-lipidemic, anti-neoplastic, and anti-diabetic activity. In this study, we evaluated the anti-inflammatory efficacy of berberine on allergic airway inflammation by targeting epithelial cells. Allergic airway inflammation driven by T helper 2 (Th2)-type immunity is characterized by airway hyperresponsiveness, elevated IgE production, and eosinophilic infiltration. For eosinophil recruitment, maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 48 publications
0
20
1
Order By: Relevance
“…Eosinophilic inflammatory response, which is characteristic of asthma, is known to be induced by IL-4, IL-5, and IL-13 produced by CD4 + T helper type 2 (Th2) cells [ 21 ]. Furthermore, proinflammatory cytokines such as TNF-α, IL-6, and IL-1β, function as growth factors for B cells and play an important role in the differentiation of CD4 + Th2 cells [ 22 ]. These cytokines have been reported to increase the secretion of mucus by stimulating goblet cells of bronchi, resulting in AHR [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilic inflammatory response, which is characteristic of asthma, is known to be induced by IL-4, IL-5, and IL-13 produced by CD4 + T helper type 2 (Th2) cells [ 21 ]. Furthermore, proinflammatory cytokines such as TNF-α, IL-6, and IL-1β, function as growth factors for B cells and play an important role in the differentiation of CD4 + Th2 cells [ 22 ]. These cytokines have been reported to increase the secretion of mucus by stimulating goblet cells of bronchi, resulting in AHR [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilic in ammatory response, which is characteristic of asthma, is known to be induced by IL-4, IL-5, and IL-13 produced by CD4 + T helper type 2 (Th2) cells [20]. In addition, proin ammatory cytokines, such as TNF-α, IL-6, and IL-1β, function as growth factors for B cells and play an important role in the differentiation of CD4 + Th2 cells [21]. These cytokines have been reported to increase the secretion of mucus by stimulating the goblet cells of bronchi, resulting in AHR [22,23].…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Signal transducer and activator of transcription 6 regulates Th2 cell differentiation and mediates IL-4/IL-13-induced eotaxin (CCL11) production, resulting in eosinophilic infiltration. 12 , 13 Recently, the STAT6 signaling pathway has gained increasing attention in the field of nasal allergic diseases. It was found that phosphorylated STAT6 (p-STAT6) was overexpressed in the sinonasal tissues of an eosinophilic CRSwNP mouse model.…”
Section: Introductionmentioning
confidence: 99%